Analisis Proksimat dan Ultimat Terhadap Total Sulfur dan Nilai Kalori pada Batubara (PT Geoservices Samarinda) - Fajarwati, Delia Aurora; Lepong, Piter; Wahidah, Wahidah (GEOSAINS KUTAI BASIN, 2023)
The price of coal in the market is largely determined by the caloric value. To find out what parameters affect the calorific value, it is necessary to do a correlation between the calorific value, inherent moisture, ash content and volatile matter contained in the coal where these contents are found in the proximate analysis and the carbon, nitrogen and hydrogen content in the ultimate analysis. In this study, apart from correlating the proximate data and ultimate data with calorific value, these two data were also correlated with total sulfur because sulfur greatly impacts the environment, so it is necessary to ensure that the amount is below the set threshold. The correlation used is Pearson Correlation. Determination of coal classification using standards Americans Society For Testing & Materials (ASTM). Correlation test results showed that total sulfur had a very strong correlation with inherent water content, volatile matter content, fixed carbon and hydrogen content. The calorific value correlates very strongly with the inherent water content, fixed carbon and nitrogen content. However, total sulfur and calorific value did not correlate with ash content. The coal classification of the five samples is included in the sub-bituminous class with a calorific value range of 10,500 Btu/lb - 8,300 Btu/lb.